The play way : an essay in educational method / by H. Caldwell Cook. - Cook, Henry Caldwell, 1886-1939. (Tufts University. Tisch Library., 2015)
2d ed.; 1 online resource (xvi, 366 pages, [15] leaves of plates) : illustrations (some color, 1 folded); Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.